Are the foreign stores more valuable than the local? A regional survey on large-scale retailers in Taiwan - F. C., Frank Pan (Advances in Aquaculture and Fisheries Management, 2020)
This paper examined the effects of consumer ethnocentrism on perceived service quality, perceived-value, and accordingly, loyalty in a context of large-scale retail stores. This research proposed that consumer ethnocentricity may have effects on perceived-value and loyalty in this particular service business. Consumers to the stores of three forms of ownership are surveyed and analyzed in this study. 340 female consumers were invited from stores of an international joint venture (IJV), a foreign direct investment (FDI) and a domestic to complete the questionnaire right after their shopping journey. Study results indicated that the effects of consumer ethnocentricity on purchasing behaviour were more possible to stem from the patriotism than the alien-phobia. Although a direct effect of consumer ethnocentricity on loyalty was not apparent, consumers who were low in ethnocentricity were inclined to prefer shopping with foreign services than the domestic. The research suggested that fostering the unique competitive advantages was necessary for the domestic business other than claiming for national patriotism